Parental risk attitudes and children's secondary school track choice - Guido Heineck; Oliver Wölfel (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
It is well known that individual's risk attitudes are related to behavioral outcomes such as smoking, portfolio decisions, and also educational attainment, but there is barely any evidence on whether parental attitudes affect the educational attainment of dependent children. We add to this literature and examine whether parent's risk attitudes relate to children's secondary school track choice in Germany where tracking occurs at age ten and has a strong binding character. Our results indicate mainly no effects of paternal risk preferences but a strong negative impact of maternal risk aversion on children's enrollment in upper secondary school. – – In zahlreichen Studien zeigt sich der Einfluss von Risikobereitschaft auf individuelles Verhalten in unterschiedlichen Bereichen wie etwa Rauchen, Portfolioinvestitionen und auch Bildungsentscheidungen. Es gibt jedoch kaum Evidenz darüber, ob und welchen Einfluss Risikoeinstellungen von Eltern auf das Bildungsverhalten von Kindern ausüben. In der Studie untersuchen wir nun die Auswirkungen der elterlichen Risikoeinstellung auf die Sekundärschulwahl von Kindern. Die Ergebnisse deuten auf keinen großen Einfluss der väterlichen Risikoeinstellung hin, jedoch auf substantiell negative Auswirkungen mütterlicher Risikoaversion auf die Wahl des Gymnasiums.
Keywords: I21; J24; 330; educational choice; risk attitudes; SOEP; Eltern; Risikopräferenz; Kinder; Bildungsverhalten; Weiterführende Schule; Schätzung; Deutschland